ANALISIS PENGGUNAAN METODE PEMBALIKAN BEBAN PEMBUKTIAN DALAM TINDAK PIDANA PENCUCIAN UANG (Money Laundry) - Supriadin Supriadin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
countries with civil law systems such as those in Indonesia, fettered by the dogmatic paradigm led to the application of normative-legal formalities are usually constrained problem. Though many variations of crimes not yet covered by the rule of positive law in this country. Moreover, many legal rules that were tumpan provisions overlap with another rule of law. So it is not uncommon in a world of justice, the judge's decision with regard to the issue raised controversy in the community. If this happens, efforts to conduct groundbreaking law was supposed to be done with the use of methods that are in line with the concept of handling the legal problems that occur. This is important, including in dealing with certain criminal cases, especially criminal pencuciang money using the method of proof process of reversal of the burden of proof (omkering van de bewijslast).